Integrated transcriptomic analysis of LMB2-induced podocyte injury identifies conserved inflammatory and adaptive stress responses - Mohammad-Reza Esmaeili; Marjan Nejati; Shaqayeq Roqanian; Reza Moghadasali; Sara Taleahmad (PLoS ONE, 2026)
Podocyte injury is a central driver of progressive glomerular diseases, yet the temporal organization of podocyte-intrinsic responses remains incompletely defined. In this study, we performed an integrated re-analysis of two publicly available mouse transcriptomic datasets (GSE108629 and GSE151869) to identify conserved molecular responses to LMB2-induced podocyte injury across comparable post-injury time points. Differential expression analysis was conducted independently at Day 4 and Day 7 in each dataset, followed by cross-dataset integration at each time point by identifying shared differentially expressed genes (DEGs) with consistent directionality. The resulting Day 4 and Day 7 shared gene sets were subsequently combined to define a final pooled shared DEG set. Functional enrichment, network analysis, upstream regulator prediction, and gene set enrichment analysis (GSEA) were used to characterize conserved biological processes and regulatory features. We identified 1,418 and 1,401 shared DEGs at Day 4 and Day 7, respectively, with 725 genes defining the final pooled shared DEGs set. At Day 4, the transcriptional response was characterized by inflammatory signaling and adaptive stress-related pathways, including endoplasmic reticulum stress. By Day 7, this response expanded to include extracellular matrix remodeling, focal adhesion reorganization, sustained inflammatory signaling, and downregulation of autophagy–lysosome pathways, together with disruption of ER-to-Golgi trafficking. Network analysis highlighted RELA-centered regulatory modules alongside epigenetic- and kinase-associated regulators. Collectively, these findings support a conserved, cross-dataset biphasic transcriptional response to podocyte injury, characterized by an early adaptive inflammatory phase followed by a later maladaptive state involving extracellular remodeling and impaired proteostasis. This framework provides a reproducible, temporally organized injury signature and is consistent with stage-specific pathways as potential targets for future mechanistic and therapeutic studies.